2012
DOI: 10.1080/15427528.2012.696085
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity Among Indian Coffee Cultivars Determined via Molecular Markers

Abstract: Information on genetic diversity of different commercial coffee cultivars grown in India during the last 90 years is scarce.In the present study, the genetic diversity of selected coffee cultivars, along with some advanced breeding lines, was evaluated using random amplified polymorphic DNA (RAPD), inter-simple sequence repeat (ISSR), and sequence-related amplified polymorphism (SRAP) markers. The average polymorphism information content (PIC) or the genetic diversity of ISSR primers (0.365) was higher than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…The genetic variability of C. arabica accessions from other countries, such as Costa Rica [94], Mexico [95], Nicaragua [96], India [97][98][99], Indonesia [100], China [101], Kenya [102] and Ethiopia [34,[103][104][105], has also been analyzed using markers such as ISSRs, SSRs, sequence-related amplified polymorphisms (SRAPs), AFLPs, and SNPs. In Ethiopia, different studies have shown the presence of great genetic variability in coffee plants.…”
Section: Genetic Diversity Based On Molecular Markersmentioning
confidence: 99%
“…The genetic variability of C. arabica accessions from other countries, such as Costa Rica [94], Mexico [95], Nicaragua [96], India [97][98][99], Indonesia [100], China [101], Kenya [102] and Ethiopia [34,[103][104][105], has also been analyzed using markers such as ISSRs, SSRs, sequence-related amplified polymorphisms (SRAPs), AFLPs, and SNPs. In Ethiopia, different studies have shown the presence of great genetic variability in coffee plants.…”
Section: Genetic Diversity Based On Molecular Markersmentioning
confidence: 99%
“…The importance of DNA-based markers in accurately detecting genetic factors in coffee was reported by Lashermes et al (1996). Several researchers have reported the presence of a low level of genetic diversity and a narrow genetic base of commercial varieties of arabica coffee using different molecular markers, such as amplified fragment length polymorphisms (AFLPs) (Steiger et al 2002;Maluf et al 2005), restriction fragment length polymorphisms (RFLPs) (Anthony et al 2002), random amplified DNA polymorphisms (RAPDs) (Maluf et al 2005;Silvestrini et al 2008;Mishra et al 2012), inter simple sequence repeats (ISSRs) and sequence-related amplified polymorphisms (SRAPs) (Mishra et al 2012;Jingade et al 2019) and SSR markers (Anthony et al 2002;Maluf et al 2005;Silvestrini et al 2007;Teressa et al 2010;Geleta et al 2012;Al-Murish et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A number of works on the assessment of arabica diversity have been carried out with differing results. In general, among three main types of material (cultivar/varieties; accessions/introgression/hybrids; and spontaneous/sub‐spontaneous) almost all studies show a very low genetic variation amongst arabica cultivars using different marker systems [random amplified polymorphic DNA (RAPD), amplified fragment length polymorphism (AFLP), simple sequence repeat (SSR), Inter Simple Sequence Repeat (ISSR), Sequence‐Related Amplified Polymorphism (SRAP), Target Region Amplification Polymorphism (TRAP)] and coffee collected from different regions (Brazil, Yemen, India, Australia and Vietnam, Tanzania, Hawaii) . The second group (accessions/introgression/hybrids) shows low to significant variation, more diverse in the introgressed lines .…”
Section: Coffee Genomic Resourcesmentioning
confidence: 99%